“The Spiritual Power of Matter” - Sequeiros, Leandro (Razón y fe, 2019)
One of the most original and controversial intuitions of Pierre Teilhard de Chardin (1881-1955) is that physical matter includes in its interior a potential capacity to expand, evolve and ascend towards the Spirit. There is no ontological split between Matter and Spirit. Both are stages of the same process of complexification and ascension of Matter into Spirit. This intuition is already present in Teilhard’s early writings of 1916 written on the battle front. This intuition will mature during his “baptism of reality” in the trenches of the First World War and is synthesized in his essay of 1919, The Spiritual Power of Matter.